Strategi Kebijakan Pemerintah Daerah: Peningkatan Kapasitas Produksi, Penyerapan Tenaga Kerja dan Peningkatan Pendapatan UMKM - Abd Rahman Alatas; Rahmat Pontoh; Ayuwandira M Morad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the influence and analysis of local government policy strategies on increasing production capacity, employment, and increasing income of Micro, Small and Medium Enterprises (MSMEs) in Buol district. This study uses a quantitative research design with correlation inferential statistics. Data sources are primary and secondary data, namely data obtained from observations, interviews, questionnaires, and documentation. In this study 102 respondents as a sample of Micro, Small and Medium Enterprises (MSMEs) in Buol District. The data analysis technique used is a multiple linear regression model. From the results of the research and discussion of the data analysis that has been carried out, it is known that the local government's policy strategies have an effect on increasing the production capacity of Micro, Small and Medium Enterprises (MSMEs). further Government policy strategies affect the employment of Micro, Small and Medium Enterprises (MSMEs). Furthermore, the government's policy strategy has an effect on increasing the income of Micro, Small and Medium Enterprises (MSMEs). Furthermore, the increase in production capacity will affect the employment of Micro, Small and Medium Enterprises (MSMEs). and Increasing production capacity affects the income of Micro, Small and Medium Enterprises (MSMEs).